PROSPECTS OF TRANSFORMATION OF THE COMPETENCE PARADIGM OF UKRAINIAN LANGUAGE FOR PROFESSIONAL PURPOSES - Humeniuk, Iryna; Bagriy, Mariya (Mountain School of Ukrainian Carpaty, 2023)
Currently, the competence paradigm is a strategic direction for the development of higher education. There has objectively arisen a need to transform the existing and develop new methodical training systems aimed at forming a set of competences necessary for students’ successful professional activity. The article analyzes the competence paradigm of the educational discipline Ukrainian Language for Professional Purposes through the prism of the peculiarities of training specialists in the pedagogical field. The specifics of the research have necessitated using a complex of theoretical, empirical, visual and graphic methods. To establish the coverage frequency of the competence paradigm components of the academic discipline (tasks 1 and 2 of the study), the methods of scientific sources analysis, synthesis, generalization, abstraction, and comparison have been used. In order to fulfill the third task of the research, the methods of observation, self-observation, comparison, and description have been applied. Visual methods (diagram construction) have been used to form a synthesized idea of the research results. Within the article, an analysis of the scientific information space is carried out regarding the coverage of the methodical aspects of implementing the linguodidactic competence paradigm in the context of Ukrainian Language for Professional Purposes. It has been established that the study of the academic discipline potential of competence-based training of future teachers began in 2004. Special attention in research is paid to the formation of the communicative, linguistic, speech, lexical, and terminological competences of future specialists in various specialties. Instead, the methodical aspects of formation of the documentary, linguocultural, country studies, general scientific, megapragmatic, entrepreneurial, intercultural, gender, and ecological competences remain relevant but understudied. The possibilities of formation of the media, project, ethical, reflexive, prognostic, aesthetic, visual, phonological, orthoepic, orthographic, grammatical, and phraseological competences of students of higher pedagogical education in the context of Ukrainian Language for Professional Purposes have not yet been the subject of scientific investigations in Ukrainian linguodidactics. The article organizes the components of the competence paradigm of Ukrainian Language for Professional Purposes in relation to their coverage frequency in works by modern scientists. The dynamics of the study into the competence paradigm of the specified academic discipline are traced in the chronological aspect. The compliance of its components with the Standard of Higher Education in Specialty 013 Primary Education for the first (bachelor) level of higher education, as well as the educational and professional program Primary Education, was established.